Carbon-free hydrogen and bioenergy production through integrated carbon capture and storage technology for achieving sustainable and circular economy– A review. (15th June 2023) - Nandhini, Rajendran; Sivaprakash, Baskaran; Rajamohan, Natarajan; Vo, Dai-Viet N.
Highlights: Biological sequestration techniques for CO2 reduction are described. Bioenergy with carbon capture and storage concept is reviewed. The economic feasibility and environmental outlook are reviewed. A novel illustration of the artificial photosynthesis process is addressed. Abstract: Drastic changes in climatic conditions accelerate the need for the implementation of emission reduction techniques to restrict global warming. Conventional technologies do face severe drawbacks in reducing carbon emissions. Carbon neutrality is considered as the most essential concept as it can alleviate the issues of greenhouse gas emissions while deriving energy and fuels from fossil origin. Several reduction technologies are proposed in the recent past, in which the integration of renewable energy resources such as solar and wind power are signified. The review aims to provide an understanding of the technology transition to attain carbon neutrality through production of carbon-free energies such as hydrogen and bioenergy. Despite the chemical and physical sequestration methods, the biological sequestration technique is given special attention for the mitigation of CO2 emissions by utilizing photosynthetic microalgae. Of numerous microalgae, Chlorella vulgaris, a common eukaryotic microalga found in freshwater showed a maximum CO2 fixation rate of about 3.35 g/L/d with 10 % CO2 input. Apart from capturing and storing carbon in the geological site, the concept of utilizing and converting carbon into valuable byproducts is described elaborately. The possibilities for utilizing renewable energy sources for carbon-free energy production through unique prototypes are reviewed and elaborated. It mainly aids to utilize renewable resources more than conventional, which significantly minimizes the carbon footprint. The integration of bioenergy, carbon capture and storage concepts with renewable energy sources extends opportunities to minimize emissions and transition towards carbon neutrality and indeed can aid in achieving carbon negativity. The aforementioned concept was reported to produce about 12.5 million tons ton of hydrogen with 133 million tons of CO2 recovery. An innovative prototype to resolve emission issues other than CO2 was also addressed. Illustrations of the artificial photosynthesis process, convective vortex system and integrated multi energy system are disc proposed innovative carbon reduction technologies' economic feasibility and environmental outlook technologies are reviewed and presented.